2020
DOI: 10.1002/ctm2.225
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic stemness biomarker CCDC80 reveals acquired drug resistance and immune infiltration in colorectal cancer

Abstract: To the Editor, Colorectal cancer (CRC) is a malignance ranking the third cause of death in malignant tumors. 1 The high mortality of CRC is mainly caused by frequent postoperative metastasis and multidrug resistance. 2 A group of cancer stem cells (CSCs) have been discovered in CRC and the mRNA expression-based stemness index (mRNAsi) was considered as a novel indicator to measure cancer development and drug resistance. 3,4 In the present study, we first explored the prognosis of mRNAsi in CRC patients and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…The clinical significance of CCDC80 in malignant tumors was attractive. In previous studies, CCDC80 was reported as a prognostic signature in serous ovarian carcinoma, colorectal cancer, and muscle-invasive bladder cancer [26][27][28]. However, no study has revealed the discriminatory capacity of CCDC80 in malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of CCDC80 in malignant tumors was attractive. In previous studies, CCDC80 was reported as a prognostic signature in serous ovarian carcinoma, colorectal cancer, and muscle-invasive bladder cancer [26][27][28]. However, no study has revealed the discriminatory capacity of CCDC80 in malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 For example, CCDC80 is the core regulator for self-renew in haematopoietic stem/progenitor cell, 47 which functions as a stemness biomarker in CRC. 48 In addition, Yang et al 49 have reported that CCDC25 enhances metastasis via activation of the ILK-β-parvin pathway in tumour cells. Therefore, it is conceivable that CCDC137 might promote proliferation, CSC characteristics and metastasis in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al verified that high levels of MFAP4 expression predict platinum-based chemotherapy resistance and imply a poor prognosis in patients with serous OC [ 45 ]. CCDC80 is a common tumor stemness marker used in a variety of solid tumor prognostic models [ 46 , 47 , 48 ]. Studies have shown that it helps tumor cells acquire drug resistance and immune infiltration [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…CCDC80 is a common tumor stemness marker used in a variety of solid tumor prognostic models [ 46 , 47 , 48 ]. Studies have shown that it helps tumor cells acquire drug resistance and immune infiltration [ 46 ]. USP1 is one cause of drug resistance in tumors, allowing them to evade chemotherapy by modulating the p38 pathway and activating the MAPK pathway [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%